Interface development for rendering eXpressive B-spline curves - Wee, Kenze Hon-Ming (Nanyang Technological University, 2025)
A key component of digital design is vector graphics, which enable designers to scale images without losing quality. Based on prior vector-based stroke modelling and rendering research, Hock Soon Seah et al. created the eXpressive B-Spline Curve (XBSC). These vector curves mimic the shape structure of Chinese calligraphic strokes and appearance through flexible colouring management and shape property control. However, the process of creating the curves is unintuitive and tedious. This project aims to develop a graphic user interface (GUI) application known as XBSCreate to facilitate a user-friendly experience in creating, rendering, and saving XBSC strokes. The application is created in the Unity game engine with the C# programming language. The report discusses the brief history and mechanics of XBSC, from Bézier to Disk B-spline curves, as well as the state of the previous prototype implementation. An overview of XBSCreate and a comparison of features between the previous prototype are presented, highlighting the difference in steps taken and additional feature requirements. The technical implementation of key classes and their functions are then elaborated on. Lastly, current limitations and recommendations for further work on the project are examined.